Prediction of rodent carcinogenicity using the DEREK system for 30 chemicals currently being tested by the National Toxicology Program. The DEREK Collaborative Group. - Marchant, C A (1996)
DEREK is a knowledge-based expert system for the qualitative prediction of toxicity. The DEREK system has been used to predict the carcinogenicity in rodents of the 30 chemicals in the second National Toxicology Program (NTP) carcinogenicity prediction exercise. Seven of the chemicals were predicted to be carcinogens. For 23 chemicals, there was no evidence in the DEREK knowledge base to suggest carcinogenic activity. Supplementary data from a variety of sources have been evaluated by human experts to assess confidence in each DEREK prediction. These sources included standard toxicology reference texts, genotoxicity and subchronic toxicity assay results for each chemical, as well as Salmonella mutagenicity and carcinogenicity data for close structural analogues. This process has led to the proposal of a number of improvements to the DEREK carcinogenicity knowledge base.